Reirradiation in Head and Neck Recurrent or Second Primary Tumor: Efficacy, Safety, and Prognostic Factors. Issue 5 (September 2015) - Buglione, Michela; Maddalo, Marta; Mazzeo, Ercole; Bonomo, Pierluigi; Spiazzi, Luigi; Bruni, Alessio; Paiar, Fabiola; Triggiani, Luca; Greto, Daniela; Rubino, Laura; Livi, Lorenzo; Bertoni, Filippo; et al.
Aims and background: We investigated efficacy, safety, and prognostic factors of reirradiation in patients with recurrent or second primary head and neck cancer. Methods: Records of 75 consecutive patients treated with reirradiation between August 2005 and December 2013 were reviewed. Results: Median overall survival (OS) and cancer-specific survival (CSS) were 29.5 and 33.6 months. Median local control (LC) and progression-free survival (PFS) were 21.7 and 16.2 months. Univariate analysis showed that patients younger than 70 years, with a Karnofsky Performance Status (KPS) >90 or with 2 or less comorbidities at time of reirradiation, have a better OS; KPS >90 and biological equivalent dose (BED) >72 Gy positively influenced the PFS. At multivariate analysis, KPS at reirradiation was an independent predictive factor for OS, while BED was an independent predictive factor for CSS and OS. At univariate analysis, patients with planning target volume (PTV) >221 mL had worse LC and PFS rates, with results confirmed at multivariate analysis. The rate of fatal treatment-related adverse events was 6.7% (3 carotid blowout, 1 soft tissue necrosis, and 1 thromboembolic event). Conclusions: This study confirms the role and outcomes of reirradiation. A careful selection of patients could minimize acute and late side effects and influence survival: elderly patients, with significant medical comorbidities or poor KPS, are worse candidate for reirradiation. Total dose delivered with reirradiation and PTV appear to be other potential prognostic factors. Further studies of dose escalation are needed to establish the total dose that could achieve better LC rates with a safer toxicity profile.